Dissemination of Sharia Cooperatives at KSP Astek - Dwiny Meidelfi; Rika Idmayanti; Rita Afriyenni; Sri Yusnita; Eliyanora (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
KSP Astek is a conventional-based savings and loan cooperative founded by a community association in Astek housing, Padang City, West Sumatra in 1991. Sharia Cooperative Training as community service, providing new enlightenment and trust for KSP Astek members in developing their business through Sharia-based cooperatives. With an adult or participatory training approach, participants gain further understanding and enthusiasm about Sharia Cooperatives. Sharia Cooperatives are cooperatives whose principal activities, objectives, and business activities are based on Islamic sharia, namely the Qur'an and Sunnah. Sharia Financial Services Cooperative is a cooperative whose business activities are in the fields of financing, investment, and savings according to the pattern of profit sharing (sharia). This community service activity provides knowledge about sharia cooperatives to members of KSP Astek. The sharia cooperative was chosen by KSP Astek because it is more in line with belief and in principle, it is more suitable during the pandemic because of the profit-sharing system that is applied. This community service activity was carried out in May 2022. The material provided included the introduction of sharia cooperatives, the basis of sharia cooperatives, the objectives of sharia cooperatives, the principles of sharia cooperatives, sharia cooperative businesses, the history of sharia cooperatives, the sharia financial system, and the underlying principles. Islamic financial system, and characteristics of Islamic transactions.